Perjuangan Perempuan Dalam Novel Mereka Bilang Aku Kemlinthi Karya Hanifa Vidya - Aufa Azkia (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The following article discusses the results of research on the value of women's struggle in the novel They Bilang Aku Kemlinthi by Hanifa Vidya with a mimetic approach. The focus of this discussion is to describe values ​​which include social reality, educational reality, and the reality of struggle. This approach can be linked between literary works and real life through a mimetic approach. In the novel, the local community rejects the "cook, macak, manak" system, that women can only cook, dress up and give birth. So researchers are interested in studying it using a mimetic approach. The method used in this article is a qualitative descriptive approach which produces data in the form of written words, and this research contains data quotations which provide an overview of the research results, then the data collection technique used is reading and note-taking techniques, because to find out a picture of life social values, education, and struggles that exist in real life. The description of social reality includes an attitude of helping the upper class to the lower class (compassion), and the existence of an attitude of helping the lower class to the upper class (reciprocity) in the novel reflects social values ​​in real life. Then the description of the reality of education, such as enthusiasm for education and being active in school activities, in the novel, the value of education is still present in the real world. Then the reality of struggle is related to fighting for rights.